Methods of teaching computer science in the system pedagogical knowledge - Nadyrova, F K; Zhanys, A B; Mubarakov, A M (IOP conference series. Materials Science and Engineering, 2020)
Modernization of education began to wear a permanent, permanent character in the modern world, since the dynamics of changes in the needs of individuals, society and the state for education is steadily growing. For quite a long time, the main subject of the modernization of school education was its content. However, in recent years, it has become increasingly clear that the center of gravity of the renewal and development of education should be shifted towards methods, innovative forms and means of education. The system-activity approach as a methodology for constructing state standards of general education closely links educational results with certain types of schoolchildren's learning activities. It is clear that the use of new types of educational activities will force to look for new innovative forms of their implementation. The subject of the methodology of teaching informatics and a place in the vocational training system for an informatics teacherComputer science as a science and a subject in school. The connection of teaching methods of computer science with pedagogy, psychology and computer science. Methodical system of teaching computer science in a secondary school. General characteristics of its main components (goals, content of training, methods, forms and means of training).